2022
DOI: 10.1093/heapol/czac092
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the prioritization of vaccines by policymakers in low- and middle-income countries: a scoping review

Abstract: Vaccination decision making in low-and-middle-income countries (LMICs) has become increasingly complex, particularly in the context of numerous competing health challenges. LMICs have to make difficult choices on which vaccines to prioritize for introduction while considering a wide range of factors such as disease burden, vaccine impact, vaccine characteristics, financing, health care infrastructures, whilst being adapted to each country’s specific contexts. Our scoping review reviewed the factors that influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Through a data-driven, age-strati ed epidemic model to evaluate the effects of Covid-19 vaccine inequities focused on 20 LMICs from all WHO regions, it has been revealed that as of October 1, 2022, 77% of individuals in high and upper middle income countries completed the initial vaccination course, with its equivalent in LMICs being 50% [49]. In this same study, the vaccine coverage by October 1, 2021 in HICs was more than 1 dose per person while that of lower middle income countries was 40 doses per 100 and low income countries stood at 3.6 doses per 100, with these inequalities further discussed in several other studies [50,51,52,54,55]. In HICs, challenges related to vaccine hesitancy and dose scarcity have been anticipated, with governments implementing potential solutions like mass media interventions and population groups prioritization to increase uptake.…”
Section: Discussionsupporting
confidence: 54%
“…Through a data-driven, age-strati ed epidemic model to evaluate the effects of Covid-19 vaccine inequities focused on 20 LMICs from all WHO regions, it has been revealed that as of October 1, 2022, 77% of individuals in high and upper middle income countries completed the initial vaccination course, with its equivalent in LMICs being 50% [49]. In this same study, the vaccine coverage by October 1, 2021 in HICs was more than 1 dose per person while that of lower middle income countries was 40 doses per 100 and low income countries stood at 3.6 doses per 100, with these inequalities further discussed in several other studies [50,51,52,54,55]. In HICs, challenges related to vaccine hesitancy and dose scarcity have been anticipated, with governments implementing potential solutions like mass media interventions and population groups prioritization to increase uptake.…”
Section: Discussionsupporting
confidence: 54%
“…The decision-making environment for new vaccine introduction in LMICs is complex given the range of immunization strategies and activities available to countries, combined with economic and financial constraints many LMICs face [ 9 ]. Decision-making about new vaccine introductions, including strategic decisions about medium- to short-term priority vaccines for introduction, requires the simultaneous consideration of multiple criteria that collectively capture the broader value of vaccines in terms of benefits and impact across the vaccine life cycle, referred to by WHO as the “full value of vaccines” [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decision-making environment for new vaccine introduction in LMICs is complex given the range of immunization strategies and activities available to countries, combined with economic and financial constraints many LMICs face [ 9 ]. Decision-making about new vaccine introductions, including strategic decisions about medium- to short-term priority vaccines for introduction, requires the simultaneous consideration of multiple criteria that collectively capture the broader value of vaccines in terms of benefits and impact across the vaccine life cycle, referred to by WHO as the “full value of vaccines” [ 9 , 10 ]. A recent systematic review of criteria considered in national decision-making for the introduction of new vaccines showed that, indeed, many criteria are considered, noting that programmatic and acceptability aspects were not as often considered and that NITAGs increasingly take into consideration economic evaluations [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently monitoring dengue epidemiology before and after introducing the dengue vaccine on a large scale can help demonstrate its effectiveness, especially on the dengue burden and prevalence across serotypes [ 18 ]. Furthermore, economic evidence showcasing the cost-effectiveness and societal impact of consistently implementing dengue vector control and vaccination programs is crucial for gaining government buy-in [ 19 ]. To complete the evidence requirements, emphasizing patient voices with real-life stories can shed light on the individual-level burden of dengue.…”
Section: Discussionmentioning
confidence: 99%